The Influence Of Work Life Balance, Emotional Intelligence And Work Environment On Employee Performance Puskesmas Klatak Banyuwangi - Kusumawati, Diva Hanessa; Hakim, Arif Rahman; Fahrurrozi, Moh (Neo Journal of economy and social humanities, 2024)
The purpose of this study was to determine the effect of work life balance, emotional intelligence, and work environment on the performance of Klatak Health Center employees. The population of this study were employees of the Klatak Health Center, Banyuwangi Regency, East Java. The data collection method of this study used a questionnaire distributed to 52 samples of Klatak Health Center employees. This research method used is multiple linear regression, t test, and F test. The results showed that work life balance variables, emotional intelligence and work environment simultaneously affect employee performance. Emotional intelligence and work environment variables partially affect employee performance while work balance variables have no effect on employee performance at the Klatak Banyuwangi Health Center.